Dynamic behavior and vulnerability analysis of bridge columns with different cross-sectional shapes under rockfall impacts. (August 2020) - Xie, Ruihong; Fan, Wei; Liu, Bin; Shen, Dongjie
Abstract: Rockfall disasters pose a significant threat to bridge structures in mountainous areas. Most of the destroyed bridge structures in mountainous regions are impacted by rockfalls to different degrees. Reinforced concrete (RC) columns with circular and square cross-sections are extensively used in bridge structures as typical alternatives, because of their advantages of easy construction and good performance. Although their seismic behaviors have been extensively investigated, limited studies have been devoted to exploring their dynamic responses and vulnerability to rockfall impacts. To this end, detailed finite element (FE) models were established in this study, to investigate the dynamic behavior and vulnerability of bridge structures with different cross-sections subjected to rockfall impact loading. Key modeling issues, such as modeling RC columns under both impact loading and the initial permanent loads prior to impact, were examined and addressed by high-resolution FE simulations. The effects of the rockfall diameter, impact velocity, and impact height on the dynamic behaviors of the columns, such as the impact force, lateral displacement, and residual axial capacity, were carefully investigated by using the calibrated FE models. Comparison of the dynamic behaviors of the circular and square columns indicated that the impact-resistance performance of the former was remarkably superior to that of the latter, for the same amount of materials used. A vulnerability analysis procedure based on the response surface model and Monte Carlo simulations was proposed, to investigate the probability of various damage levels for both the circular and square columns under rockfall impacts. Good agreement was achieved for the impact-induced responses obtained from the high-resolution FE simulations and the surrogate response surface models. The vulnerability analysis results further confirmed the disadvantage of the square columns for application in mountainous areas, owing to a relatively high risk of rockfall impact. The vulnerability analysis procedure proposed in this paper will assist researchers to investigate the damage and vulnerability of RC column structures subjected to impact loading.